2022
DOI: 10.33759/asta.v2i1.182
|View full text |Cite
|
Sign up to set email alerts
|

Upaya Peningkatan Pengetahuan Siswa SMK/SMA Mengenai Kosmetik yang Aman dengan Metode Daring

Abstract: The rise of media coverage regarding the production of illegal and dangerous cosmetics is one proof that the use of cosmetics is currently a necessity. Online marketing is one of the facilities for spreading these illegal cosmetics. Thus, it is necessary to educate the public, especially social media users who are generally in productive age range, to be more careful in choosing safe cosmetics. In this community service activity, education was carried out to 17 participants from senior high school student. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Kemudian, guna melindungi pelanggan, BPOM sudah menyediakan legalitas dari suatu produk obat, makanan, dan kosmetik secara mandiri untuk masyarakat lewat web bpom (Arifiyana et al, 2022). Saat ini pada industri kosmetik, kosmetik termasuk kedalam jenis produk yang memiliki jumlah produk pengganti yang sangat banyak dibandingkan dengan industri lainya, sehingga pelanggan dapat dengan gampangnya untuk beralih kepada merek lain yang dinilai sesuai dengan keinginan dan kebutuhan mereka masingmasing.…”
Section: A Kosmetikunclassified
“…Kemudian, guna melindungi pelanggan, BPOM sudah menyediakan legalitas dari suatu produk obat, makanan, dan kosmetik secara mandiri untuk masyarakat lewat web bpom (Arifiyana et al, 2022). Saat ini pada industri kosmetik, kosmetik termasuk kedalam jenis produk yang memiliki jumlah produk pengganti yang sangat banyak dibandingkan dengan industri lainya, sehingga pelanggan dapat dengan gampangnya untuk beralih kepada merek lain yang dinilai sesuai dengan keinginan dan kebutuhan mereka masingmasing.…”
Section: A Kosmetikunclassified
“…Apart from that, the academic infrastructure factors studied by Andrianus & Alfatih, (2023) showed that student achievement was also not influenced by academic infrastructure. Research by Arifiyana & Devianti, (2022) conducted on grade 10 TKJ students at SMK Negeri 2 Donorejo, it was said that learning intensity had insignificant results with learning independence or problem solving abilities.…”
Section: Introductionmentioning
confidence: 99%